2018
DOI: 10.5897/jvmah2018.0691
|View full text |Cite
|
Sign up to set email alerts
|

Dog breeds acquisition and owners awareness of associated surgical conditions in Nigeria

Abstract: The study evaluated dog owners' awareness of breed-associated surgical conditions in Nigeria as indices for breed choice with structured pre-tested questionnaires administered to dog owners in 17 states of Nigeria. Alsatians (36.8%) and Rottweiler (13%) breeds were mostly possessed by owners. The majority of the respondents were females (60.4%) owners. Lagos (53.4%) and Oyo (52.1%) states had the highest number of respondents while Kaduna (1.25%), Enugu (1.25%), Ekiti (1.25%), and Plateau (1.25%) states had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…It has been reported that M. canis, M. gypseum and T. mentagrophytes are the fungi responsible for more than 95% of all dermatophytoses cases in companion animals (33). Further, analysis of the results of the present study revealed a statistically significant association between the breed of dogs and occurrence of dermatophytosis as German Shepherd breed had the highest prevalence of dermatophytic infections while Lhasa Apso breed had the least prevalence (34). It has been reported that dog breed plays a significant role in the acquisition of dermatophytosis.…”
Section: Discussionsupporting
confidence: 48%
“…It has been reported that M. canis, M. gypseum and T. mentagrophytes are the fungi responsible for more than 95% of all dermatophytoses cases in companion animals (33). Further, analysis of the results of the present study revealed a statistically significant association between the breed of dogs and occurrence of dermatophytosis as German Shepherd breed had the highest prevalence of dermatophytic infections while Lhasa Apso breed had the least prevalence (34). It has been reported that dog breed plays a significant role in the acquisition of dermatophytosis.…”
Section: Discussionsupporting
confidence: 48%